Perspectives and experiences of healthcare providers on the response to the COVID-19 pandemic in three maternal and neonatal referral hospitals in Guinea in 2020: a qualitative study - Nafissatou Dioubaté; Mamadou Cellou Diallo; Cécé Maomou; Harissatou Niane; Tamba Mina Millimouno; Bienvenu Salim Camara; Telly Sy; Ibrahima Sory Diallo; Aline Semaan; Thérèse Delvaux; Lenka Beňová; Abdoul Habib Béavogui; et al. (BMC, 2024)
Abstract Background The COVID-19 pandemic has adversely affected access to essential healthcare services. This study aimed to explore healthcare providers' perceptions and experiences of the response to the COVID-19 pandemic in three referral maternal and neonatal hospitals in Guinea. Methods We conducted a longitudinal qualitative study between June and December 2020 in two maternities and one neonatology referral ward in Conakry and Mamou. Participants were purposively recruited to capture diversity of professional cadres, seniority, and gender. Four rounds of in-depth interviews (46 in-depth interviews with 18 respondents) were conducted in each study site, using a semi-structured interview guide that was iteratively adapted. We used both deductive and inductive approaches and an iterative process for content analysis. Results We identified four themes and related sub-themes presented according to whether they were common or specific to the study sites, namely: 1) coping strategies & care reorganization, which include reducing staffing levels, maintaining essential healthcare services, suspension of staff daily meetings, insertion of a new information system for providers, and co-management with COVID-19 treatment center for caesarean section cases among women who tested positive for COVID-19; 2) healthcare providers' behavior adaptations during the response, including infection prevention and control measures on the wards and how COVID-19-related information influenced providers' daily work; 3) difficulties encountered by providers, in particular unavailability of personal protective equipment (PPE), lack of financial motivation, and difficulties reducing crowding in the wards; 4) providers perceptions of healthcare service use, for instance their fear during COVID-19 response and perceived increase in severity of complications received and COVID-19 cases among providers and parents of newborns. Conclusion This study provides insights needed to be considered to improve the preparedness and response of healthcare facilities and care providers to future health emergencies in similar contexts.